A Multidisciplinary Assessment of the Phytonutrient Potential and Antimicrobial Efficacy of Vicia faba Seed Lipids: Aligning Local Resources with Viksit Bharat - Patra , Kamal Kant; Sasmal , Piu; Kumari, Abha; Mishra , Asha (American Journal of Biology and Natural Sciences, 2026)
The present study was undertaken to conduct a multidisciplinary evaluation of the phytonutrient composition, lipid profile, protein efficiency, antimicrobial efficacy, and agroecological sustainability of Vicia faba seed lipids, with the objective of aligning indigenous biological resources with the national vision of Viksit Bharat. Emphasis was placed on assessing the nutritional, therapeutic, and climate-resilient potential of this locally adaptable legume to support food security, public health, and sustainable agricultural development. Profiling of seed lipids revealed that Vicia faba possessed a modest total lipid content ranging from 1.8% to 2.5%, establishing it as a low-fat, nutrient-dense food suitable for healthy dietary formulations. The lipid fraction was dominated by essential unsaturated fatty acids, particularly linoleic acid (45.0%–58.0%) and oleic acid (18.0%–26.0%), indicating significant cardiovascular and metabolic health benefits. High levels of total phenolic content (5.8–11.3 mg GAE/g) and flavonoids (0.08–0.16 mg QE/g) were observed, confirming strong antioxidant capacity and suggesting a role in immune modulation and prevention of lifestyle-related chronic disorders. Comparative nutritional analysis demonstrated that Vicia faba exhibited superior protein content (31.5%–37.7%) compared to Cicer arietinum (19.0%–24.5%), reinforcing its value as a high-quality plant protein source. Essential amino acid profiling indicated higher concentrations of lysine (62.4 mg/g protein) and leucine (75.2 mg/g protein), supporting muscle growth, metabolic health, and nutritional adequacy in predominantly plant-based diets. The digestible indispensable amino acid score (DIAAS) ranged from 0.72 to 0.85, reflecting improved protein bioavailability and absorption efficiency. In vitro antimicrobial evaluation of seed extracts demonstrated notable inhibitory activity against both Gram-positive and Gram-negative bacterial strains. Ethanolic lipid extracts showed significant zones of inhibition against Escherichia coli (22±1.5 mm) and Staphylococcus aureus (18±0.8 mm), while aqueous extracts exhibited strong activity against Bacillus subtilis (25±2.1 mm). Moderate antifungal efficacy against Candida albicans was also observed, highlighting the therapeutic potential of Vicia faba bioactive compounds as natural antimicrobial agents. Agroecological assessment revealed that locally cultivated Vicia faba achieved high seed yields (2800–3200 kg/ha) with substantially lower water input (300–450 mm) compared to wheat, resulting in superior water-use efficiency (8.5–9.4 kg/ha-mm). Intercropping systems further optimized resource utilization, supporting smallholder resilience under water-limited conditions. Overall, the findings established Vicia faba as a nutritionally rich, antimicrobial, and climate-resilient legume with immense potential for maximum utilization. Its integration into Indian agri-food systems strongly supported the objectives of Viksit Bharat by promoting nutritional security, sustainable agriculture, and value-added utilization of local resources.